(3Gdabg GdeNUhU HJQUjY GdfUhUs - (3GdYdGFj , eMeO Hf CMeO GdYdGFj GdMfaj,J (B918 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdCMO HPGJg hcHQjGFg GdhGMO HUaGJg hESeGFg s
(3BNQgG (B:s
(3hEKHGJ GdPdg cEYJHGQ PGJ GdYHO s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B293s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJhMjO hGdedd hGdfMds